PENGARUH NIM, BOPO, LDR, NPL & CAR TERHADAP ROA BANK INTERNASIONAL DAN BANK NASIONAL GO PUBLIC PERIODE 2007 – 2011 - Tan Sau Eng (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2013)
This research has been conducted with the purpose to analyse the effect of Capital Adequacy Ratio (CAR), Operational Efficiency (BOPO), Net Interest Margin (NIM), Non Performing Loan (NPL) and Loan to Deposit Ratio (LDR), simultaneously and partially on bank performance, which was measured by Return On Asset (ROA), and to verify as well,which of the independent variables has the most dominant effect. This research is using purposive sampling technique, involving 7 public listed banks in Indonesia as samples and the data was analysed withmultiple regression method. The result shows that all the independent variables simultaneously have significant effect on ROA, while partially only NIM, LDR and NPL have significant effect. Further,the result also indicates that the variable with most dominant effect is NIM.Keywords: NIM, LDR, NPL, CAR, ROA